Ethnobotanical and ethnomedicinal research into medicinal plants in the Mt Stara Planina region (south-eastern Serbia, Western Balkans) - Snežana Jarić; Olga Kostić; Zorana Miletić; Milica Marković; Dimitrije Sekulić; Miroslava Mitrović; Pavle Pavlović (BMC, 2024)
Abstract Background Ethnobotanical research in Southeast Europe-one of the most important European hotspots for biocultural diversity-is significant for the acquisition of Traditional Ecological Knowledge related to plants as well as for encouraging the development of local environments. The current ethnobotanical research was conducted in the region of Mt Stara Planina (south-eastern Serbia), which is characterised by rich phytodiversity with a large number of endemic and relict plant species. The aim of the study was to document the diversity of uses of medicinal plants and of traditional knowledge on their therapeutic uses. Methods Ethnobotanical data was collected through both open and semi-structured interviews with locals. Fifty-one inhabitants were interviewed (26 men and 25 women), aged 30-91, and data was analysed by means of use reports, citation frequency, use values (UV), and the informant consensus factor (ICF). Results The study identified 136 vascular medicinal plant taxa and one lichen species belonging to 53 families and 116 genera. Lamiaceae (19), Rosaceae (18), and Asteraceae (17) had the highest species diversity. The plant parts most commonly used to make a variety of herbal preparations were the aerial parts (54 citations), leaves (35 citations), fruits (20 citations), flowers (18 citations), and roots (16 citations), while the most common forms of preparation were teas (60.78%), consumption of fresh tubers, leaves, roots, and fructus (6.86%), compresses (5.88%), juices (5.39%), decoctions (3.92%), 'travarica' brandy (3.92%), and syrups (2.45%). Of the recorded species, 102 were administered orally, 17 topically, and 18 both orally and topically. The plants with a maximum use value (UV = 1) were Allium sativum, Allium ursinum, Gentiana asclepiadea, Gentiana cruciata, Gentiana lutea, Hypericum perforatum, Thymus serpyllum and Urtica dioica. The highest ICF value (ICF = 0.95) was recorded in the categories of Skin and Blood, Blood Forming Organs, and Immune Mechanism. Conclusions This study shows that medicinal plants in the research area are an extremely important natural resource for the local population as they are an important component of their health culture and provide a better standard of living.